Increase systemic levels of IL-23 as a possible constitutive marker in schizophrenia. (June 2015) - Borovcanin, Milica; Jovanovic, Ivan; Dejanovic, Slavica Djukic; Radosavljevic, Gordana; Arsenijevic, Nebojsa; Lukic, Miodrag L.
Highlights: Increase serum levels of IL-23 stay elevated in all clinical phases of schizophrenia, independently of therapy. Systemic levels of IL-23 should be considered as valuable trait marker is schizophrenia. We assume that IL-23 may stimulate Th2 response as has been suggested in asthma, particularly recently found to be related to schizophrenia. Summary: Inflammation appears to play significant role in schizophrenia. IL-23 is key molecule in mediating IL-17 dependent inflammatory response. Therefore, we analyzed the serum concentrations of IL-23 levels in patients with first episode psychosis (78 subjects), in patients with acute exacerbation of schizophrenia who were already treated with antipsychotics (47 subjects) and healthy controls (35 subjects). Diagnoses were established using International Statistical Classification of Diseases and Related Health Problems, Tenth Revision (ICD-10). Psychopathology was evaluated using the Positive and Negative Syndrome Scale (PANSS) and serum levels of IL-23 were measured using sensitive enzyme-linked immunosorbent assay (ELISA). Serum levels of IL-23 were higher in patients with first psychotic episode and in patients with schizophrenia in relapse than in healthy subjects ( p = 0.000) and no difference was established between these two groups of patients before therapy. Also, after 4 weeks of antipsychotic therapy levels of IL-23 remains elevated in both groups of patients with no differences between two groups. It appears that increased level of IL-23 in psychotic patients independently of antipsychotic therapy can be a constitutive marker in this disorder.